EAST ASIA REGIONALISM AFTER THE GLOBAL FINANCIAL CRISIS - Aryanta Nugraha (Jurusan Ilmu Hubungan Internasional, 2013)
Competing analyses has debated the prospect of East Asia regionalism in the post-Global Financial Crisis. After a decade of dynamic regionalism and community-buildingambition, Asia economy seems to have decoupled from the global economy and formedan autonomous economic zone. It is at least indicated by the rise of intra-trade intensityin East Asia. Exploring the impact of the global financial crisis to the effort of establishingEast Asia regionalism, this paper argues that although the global financial crisis presentsa new opportunity for deepening the cooperation, the East Asia regionalism only achievesa slight progress. Rather than economic reasons, the origin and development of EastAsia regionalism has been mostly driven by political motivation in order to balance theinfluence among the big powers. As the result, this regionalism has been trapped intopolitical dilemma. Therefore, the regional policy responses to address the global financialcrisis indicate the progress of East Asia regionalism has been meager.